ChemInform Abstract: Crystal and Magnetic Structure of Sr2BIrO6 (B: Sc, Ti, Fe, Co, In) in the Framework of Multivalent Iridium Double Perovskites. Issue 1 (17th December 2015) - Kayser, Paula; Alonso, Jose A.; Mompean, Federico J.; Retuerto, Maria; Croft, Mark; Ignatov, Alexander; Fernandez‐Diaz, Maria T.
Abstract: Polycrystalline samples of Sr2 BIrO6 (B: In, Sc, Fe, Co, Ti) are prepared from citrate precursors using stoichiometric mixtures of Sr(NO3 )2, IrO2, In2 O3, Sc2 O3, FeC2 O4, Co(NO3 )2, and TiC10 H14 O5 in aqueous solutions of citric acid and HNO3 followed by heating of the resulting resins (600 °C, 12 h) and calcination in air (1100—1200 °C, 12 h).